Improvement of Separate Accounting at the Enterprises of Defense Industry Using Digital Technologies - A. A. Bakulina; V. V. Zemskov (Учёт. Анализ. Аудит, 2019)
The subject of the study is the analysis of existing methodological problems in the organization and maintenance of separate accounting of costs and output of military products in accordance with the state defense procurement (SDP). The same requirement applies to the production, sales, purchase of goods and services for Federal needs by certain legal entities. The transition of the defense industrial complex (DIC) enterprises to the digital economy platform requires the improvement of the quality of financial information based on the introduction of uniform methodological principles for maintaining separate accounting of income and expenditure and generating financial results. The purpose of the article is to provide methodological assistance to the management of enterprises of the defense industrial complex (DIC) in the organization and maintenance of separate accounting of income and expenses, as well as the formation of financial results by products for each contract. It is proved that to perform the tasks on the state defense procurement it is necessary to maintain separate accounting of fixed assets, material and production resources, accounts receivable and accounts payable and other assets.